Functional single nucleotide polymorphisms within the cyclin-dependent kinase inhibitor 2A/2B region affect pancreatic cancer risk. - Campa, D; Pastore, M; Gentiluomo, M; Talar-Wojnarowska, R; Kupcinskas, J; Malecka-Panas, E; Neoptolemos, J; Niesen, W; Vodicka, P; Delle Fave, G; Bas Bueno-de-Mesquita, H; Gazouli, M; et al. (Impact Journals, 2016)
The CDKN2A(p16) gene plays a key role in pancreatic cancer etiology. It is one of the most commonly somatically mutated genes in pancreatic cancer, rare germline mutations have been found to be associated with increased risk of developing familiar pancreatic cancer and CDKN2A promoter hyper-methylation has been suggested to play a critical role both in pancreatic cancer onset and prognosis. In addition several unrelated SNPs in the 9p21.3 region, that includes the CDNK2A, CDNK2B and the CDNK2B-AS1 genes, are associated with the development of cancer in various organs. However, association between the common genetic variability in this region and pancreatic cancer risk is not clearly understood. We sought to fill this gap in a case-control study genotyping 13 single nucleotide polymorphisms (SNPs) in 2,857 pancreatic ductal adenocarcinoma (PDAC) patients and 6,111 controls in the context of the Pancreatic Disease Research (PANDoRA) consortium. We found that the A allele of the rs3217992 SNP was associated with an increased pancreatic cancer risk (OR het=1.14, 95% CI 1.01-1.27, p=0.026, ORhom =1.30, 95% CI 1.12-1.51, p=0.00049). This pleiotropic variant is reported to be a mir-SNP that, by changing the binding site of one or more miRNAs, could influence the normal cell cycle progression and in turn increase PDAC risk. In conclusion, we observed a novel association in a pleiotropic region that has been found to be of key relevance in the susceptibility to various types of cancer and diabetes suggesting that the CDKN2A/Blocus could represent a genetic link between diabetes and pancreatic cancer risk.